Trait anxiety predicts the emotional valence of meaning-making in life stories: A 10-year prospective study. (November 2016) - Thomsen, Dorthe Kirkegaard; Matthiesen, Signe; Frederiksen, Yoon; Ingerslev, Hans Jakob; Zachariae, Robert; Mehlsen, Mimi Yung
Abstract: Individuals interpret events in positive and negative ways, creating positive and negative meaning in their life stories. We hypothesized that higher trait anxiety measured 10 years earlier would predict more negative meaning-making in life stories and that negative meaning-making would be related to more concurrent depressive symptoms. Participants were 272 women who had undergone fertility treatment and completed measures of trait anxiety 10 years earlier. In the present study, they described five life story events and rated these on emotional tone and meaning-making. A path analysis showed that higher trait anxiety predicted more negative meaning-making 10 years later and that negative meaning-making predicted more concurrent depressive symptoms after adjusting for baseline depressive symptoms, trait anxiety, and education. The results suggest that life stories are important to well-being. Highlights: Meaning-making may be both positive and negative. High trait anxiety predict negative meaning-making in life stories 10 years later. Meaning-making predicted depressive symptoms after control for trait anxiety.